How physical exercises ameliorate dysmenorrhea in adolescence - Wijaya, Aqsha; Anwar, Ruswana; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi; Arya, Insi Farisa Desy; Setiawan, Iwan (Jurnal Keolahragaan, 2024)
Dysmenorrhea is frequently reported by adolescents. Physical exercises is one method of overcoming the symptoms of primary dysmenorrhea. Consistent physical activity has been shown to induce the synthesis of endorphins, which function as analgesics within the body. This study presents a comprehensive review to synthesize evidence regarding the relation between physical activity or exercise with dysmenorrhea and how exercise can ameliorate dysmenorrhea in adolescents. This study followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) method to identify articles published within the last three years (2021-2023) via PubMed, Scopus, ScienceDirect, and Google Scholar. This process yielded seven pertinent studies. The studies have demonstrated that engaging in physical activity can effectively alleviate the symptoms associated with menstrual discomfort. Physical exercise in regular time for a minimum of thirty minutes, three times per week, can also contribute to the alleviation of pain associated with menstrual discomfort among adolescent females diagnosed with primary dysmenorrhea. Isometric exercise, massage therapy, yoga, electrotherapy, connective tissue manipulation, stretching, kinesio tape, progressive relaxation exercise, aviva stretching exercise, stretching exercises, core strengthening exercise and aerobic exercise are the recommended forms of physical exercise in reducing the impact of primary dysmenorrhea. However, the extent to which one experiences these benefits is contingent upon the nature and intensity of the exercise.